Infiltration Patterns and Ecological Function of Outcrop Runoff in Epikarst Areas of Southern China - Zhao, Z. (2020)
Rock outcrops (ROCs), a widespread surface component in a karst landscape, play a unique, hydrological role in the infiltration and redistribution of precipitation. This experiment aimed to explore water pathways of outcrop runoff and their ecological functions in epikarst by applying the dye tracer Brilliant Blue FCF on three sides of rocks—the uphill sides, the downhill sides, and the lateral sides—to simulate the outcrop runoff under a rainfall intensity of 100 mm h−1, combined with a soil loss survey and soil property measurements. Our results showed that the outcrop runoff infiltration in three directions (i.e., lateral flow into the soil, vertical flow, and lateral spread at the soil–rock interface) differed greatly on the three sides of the ROCs. Deep but narrow vertical flow was the most common infiltration pattern on the uphill sides; long but shallow lateral flow toward downslope dominated outcrop runoff movement on the lateral sides. However, on the downhill sides, the vertical flow at the soil–rock interface was quantitatively equal to the lateral flow to soil. The difference in outcrop runoff infiltration at the three sides of ROCs may help to reveal the mechanisms of soil erosion as well as rock dissolution and biodiversity in a karst environment.